Evaluation of the safety and efficacy of Sophorae Flavescentis Radix extract in the treatment of inflammatory bowel disease based on zebrafish models - Chen, Xiaolu; Cui, Muyao; Li, Jiaqi; Chen, Qi; Chen, Linzhen; Yang, Zhuo; Fan, Qiqi; Sheng, Yuhan; Lin, Ruichao; Ma, Zhiqiang; Zhao, Chongjun (Frontiers in Immunology, 2025)
BackgroundSophorae Flavescentis Radix (Kushen) has been employed in Traditional Chinese Medicine (TCM) for over 2,000 years, primarily for its effects in clearing heat and drying dampness, eliminating parasites, and promoting diuresis. Preliminary findings suggest that Kushen extract or its formulations may exhibit potential therapeutic benefits in alleviating inflammatory bowel disease (IBD).AimsThis study aimed to comprehensively evaluate the safety and efficacy of Kushen extract using a zebrafish model, with a particular focus on intestinal mucosal immunity, and to explore its underlying mechanisms.Material and methodsThe safety and efficacy profile of Kushen extract was comprehensively evaluated in zebrafish model. Network pharmacology combined with transcriptomics were employed to predict the mechanisms underlying Kushen extract’s therapeutic effects on IBD, followed by validation using Reverse Transcription-Quantitative Polymerase Chain Reaction (RT-qPCR) and molecular docking.ResultsAdministration of supra-therapeutic doses of Kushen extract induced hepatotoxicity effects in zebrafish, primarily manifested as hepatic morphological abnormalities and exacerbated hepatocyte apoptosis. Conversely, low-dose administration of Kushen extract demonstrated significant therapeutic benefits including improved intestinal phagocytic function, reduced gut neutrophil infiltration and enhanced goblet cell secretion. Furthermore, Kushen extract treatment at low doses significantly decreased the levels of pro-inflammatory cytokines. Integrated network pharmacology and transcriptomic analyses indicated that the amelioration of Kushen extract on IBD may be involved in FoxO4/NOD-like/Apoptosis and MAPK signaling pathways. The RT-qPCR results confirmed that Kushen extract effectively modulates the expression levels of key genes in the aforementioned pathway. Molecular docking analysis revealed binding energies of -8.1 kcal/mol between matrine and the BCL-2 protein, and -10.4 kcal/mol between oxymatrine and EGFR, indicating strong molecular interactions between these compounds and their target proteins. These interactions may collectively contribute to the therapeutic efficacy of Kushen extract.ConclusionsSupra-therapeutic doses of Kushen extract can induce marked liver damage in zebrafish. However, when administration within an appropriate dosage range, it does not elicit significant toxicity and demonstrates substantial therapeutic efficacy against IBD, partly through modulating mucosal immunity. These findings provide crucial experimental evidence to support the guidance for safe and rational clinical application of Kushen extract.